Solo Black Garlic fermented whey kefir improves sperm quality of male mice (Mus musculus) induced by lead acetate - Risda Arba Ulfa; Dina Nursaidah; Muhimatul Umami (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
Globally, men experience a decline in total fertility, characterized by a significant decline in sperm quality in terms of concentration, motility, and morphology. Environmental factors can modulate this through exposure to toxic elements, such as the heavy metal lead, in the workplace. Lead can accumulate in nature and contaminate drinking water supply systems. A series of negative responses can occur and disrupt spermatozoa production and quality. Natural ingredients, such as solo black garlic (SBG), have the potential to maintain conditions in reproductive function against the adverse effects of lead. This study utilized SBG fermented with whey kefir to investigate its effect and optimal dosage on improving spermatozoa quality in male mice induced by lead acetate. The test animals were 25 Swiss Webster male mice aged 12-14 weeks, divided into five treatment groups (n = 5 per group), namely negative control (KN), distilled water; positive control (KP), lead acetate 75 mg/kg BW; and three SBG treatment groups given lead acetate (SBG-60, SBG-120, and SBG-180). SBG was given together with lead acetate at doses of 60, 120, and 180 mg/kg BW for 30 days. The results showed SBG-120 restored concentration (31.00 × 106/ml) and motility (80.83%) toward negative-control levels; morphology abnormalities decreased by 30.50%, which were not significantly different (p > 0.05) from the negative control. Therefore, SBG with a dose of 120 mg/kg BW is optimum for maintaining spermatozoa quality in male mice exposed to lead acetate.